Observational Learning: Tell Beginners What They Are about to Watch and They Will Learn Better - Andrieux, Mathieu; Proteau, Luc (Frontiers in Psychology, 2016)
Observation aids motor skill learning. When multiple models or different levels of performance are observed, does learning improve when the observer is informed of the performance quality prior to each observation trial or after each trial? We used a knockdown barrier task and asked participants to learn a new relative timing pattern that differed from that naturally emerging from the task constraints (Blandin, Lhuisset, & Proteau, 1999). Following a physical execution pre-test, the participants observed two models demonstrating different levels of performance and were either informed of this performance prior to or after each observation trial. The results of the physical execution retention tests of the two experiments reported in the present study indicated that informing the observers of the demonstration quality they were about to see aided learning more than when this information was provided after each observation trial. Our results suggest that providing advanced information concerning the quality of the observation may help participants detect errors in the model’s performance, which is something that novice participants have difficulty doing, and then learn from these observations.